Policy Development of Inclusion Village to Fulfill the Rights of Persons with Disabilities - Bibianus Hengky Widhi Antoro; Johanes Widijantoro; Dewi Krisna Hardjanti (Jember University Press, 2021)
Stigmatization towards persons with disabilities is so pervasive in society that it directly weakens their position in various fields unlike common other people in various fields. Although Indonesia has enacted Law No. 8 of 2016 concerning Persons with Disabilities, efforts to protect and fulfil the rights of persons with disabilities must continue to be actively encouraged. This study examines one of the strategic steps being taken to protect and fulfil the rights of persons with disabilities, the development of a Village Inclusion Policy. Aside from contributing to the fulfilment of the rights of persons with disabilities, particularly in rural areas, this policy is also expected to accelerate the improvement of welfare through increased accessibility of, and participation in, rural development. The study begins by reviewing the implementation of regulations and policies related to the protection and fulfilment of the rights of persons with disabilities in general. It then analyzes the possibility of further developing the Inclusion Village Policy, drawing on a policy review, focus group discussion, and in-depth interviews with relevant stakeholders. The results of this study illustrate the strategic value of the policy as well as the various factors that encourage or inhibit the fulfilment of the rights of persons with disabilities.